Anticlotting agents and the surgical management of glaucoma. Issue 2 (March 2018) - Sozeri, Yasemin; Salim, Sarwat
Abstract : Purpose of review: A large subset of patients with glaucoma uses anticlotting agents. No standardized guidelines currently exist for managing these agents in the specific perioperative setting of glaucoma surgery. The present review focuses on currently available anticlotting agents, their influence on hemorrhagic complications following glaucoma surgery, and management strategies for their use in the perioperative period Recent findings: Anticlotting agents increase the risk of perioperative hemorrhagic complications following glaucoma surgery. Other factors that increase that risk have been identified as well, including the type of glaucoma surgery, preoperative intraocular pressure, postoperative hypotony, previous ocular surgeries, and race. Although general guidelines in the perioperative management of blood thinning agents exist, the best way to apply these guidelines specifically to glaucoma surgery remains unclear. Summary: Blood thinners are widely used and can increase the risk of hemorrhagic complications in patients undergoing glaucoma surgery. Managing these agents in the perioperative setting is challenging and should be done in collaboration with the patient's primary care provider, hematologist, or cardiologist. Management strategies should be tailored to each individual's risk of hemorrhage versus thromboembolism. Additionally, surgical plans can be modified to help minimize hemorrhagic outcomes, especially in patients who are deemed to be at high risk for perioperative bleeding.